فعالية البيع الشخصي في المؤسسات الاقتصادية الجزائرية - خويلد, عفاف (جامعة الوادي - University of Eloued, 2012)
هدفت الدراسة الحالية إلى محاولة التعرف على مدى استغلال المؤسسات الجزائرية لتكنولوجيا المعلومات والاتصال في نشاط رجال البيع الشخصي للرفع من فعاليته، وهذا بالاستعانة بمجموعة من المتغيرات المتمثلة في: طبيعة الملكية، طبيعة النشاط، طبيعة السواق التي تنشط بها المؤسسة، رقم الأعمال، وعدد العمال، إجمالي الميزانية، المستوى التعليمي للمجيب والصفة الوظيفية له. The present study aimed to identify the extent to which the Algerian ICT institutions exploit the activity of men of personal selling to increase its effectiveness, using a variety of variables such as: nature of ownership, nature of activity, nature of the markets in which the organization operates, number of works, number of workers, Total budget, educational level and functional level of respondent.
مقال
Keywords: البيع الشخصي، فعالية البيع الشخصي، تكنولوجيا المعلومات والاتصال.; Personal selling, personal selling, information and communication technology.